1995
DOI: 10.1002/ijc.2910630311
|View full text |Cite
|
Sign up to set email alerts
|

Lack of interleukin‐2 (IL‐2) expression and selective expression of IL‐10 mRNA in human renal cell carcinoma

Abstract: Freshly isolated tumor-infiltrating lymphocytes (TIL) are often functionally deficient. Since one of the key functional parameters of an immune response is the local production of cytokines, we studied the expression of cytokine genes in freshly isolated renal cancer tissue. Using a PCR-assisted mRNA amplification assay, the constitutive expression of mRNA for 10 different cytokines was assessed in renal cancer tissue. We compared the cytokine mRNA expression in freshly isolated samples of renal carcinomas, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
60
1
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(70 citation statements)
references
References 24 publications
8
60
1
1
Order By: Relevance
“…This is consistent with the undetectable or minimal cytolytic activities of purified and IL-2-expanded RCC TIL in other studies [26,[28][29][30]. IL-10 has potent inhibitory effects on cytotoxic T cell responses [31], and it is therefore possible that the production of IL-10 in the tumour microenvironment by CD4 þ TIL, as shown here and by others [12,32,33], may explain the poor cytolytic activity of CD3 þ CD8 þ TIL in RCC. The inadequate up-regulation of CD25 on CD3 þ CD8 þ TIL, but not CD4 þ TIL, following triggering by anti-CD3 may be equally relevant to their low cytolytic activity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with the undetectable or minimal cytolytic activities of purified and IL-2-expanded RCC TIL in other studies [26,[28][29][30]. IL-10 has potent inhibitory effects on cytotoxic T cell responses [31], and it is therefore possible that the production of IL-10 in the tumour microenvironment by CD4 þ TIL, as shown here and by others [12,32,33], may explain the poor cytolytic activity of CD3 þ CD8 þ TIL in RCC. The inadequate up-regulation of CD25 on CD3 þ CD8 þ TIL, but not CD4 þ TIL, following triggering by anti-CD3 may be equally relevant to their low cytolytic activity.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the relevance of effector functions mediated by in vitro grown TIL lines to the in vivo situation remains to be established, and possible artefacts involved in long-term in vitro growth of TIL limit the interpretation of numerous functional studies [12].…”
Section: Introductionmentioning
confidence: 99%
“…Our finding of high IL-10 mRNA levels in TIL is in accordance with results reported by Wang et al, who detected IL-10 mRNA in freshly-isolated lymphocyteenriched preparations from 4/5 RCC tumour specimens (Wang et al, 1995) and by Maeurer et al, who found that uncultured TIL from seven RCC patients expressed IL-10 and IL-4 mRNA (Maeurer et al, 1995). Other authors reported a high expression of IL-10 mRNA in biopsies of renal cell carcinomas (Filgueira et al, 1993;Nakagomi et al, 1995;Olive et al, 1997). A concomitant high expression of the Th2 cytokine IL-10 and the Th1 cytokine IFN-γ has been recently shown in isolated CD3 + TIL from RCC (Elsässer-Beile et al, 1999).…”
Section: Discussionsupporting
confidence: 87%
“…The detection of IL-lO mRNA in more than half of the breast tumours and the failure to detect IL-2 mRNA is consistent with previous work shown by others that IL-10 may have an inhibitory role on IL-2 production and T-cell activation. Indeed, lack of detection of IL-2 expression with selective expression of IL-10 in TILs derived from human renal cell carcinoma (RCC) was recently reported in human renal cell carcinomas, further implicating a role for IL-10 in the immunosuppression of TILs (Nakagomi et al, 1995).…”
Section: Discussionmentioning
confidence: 99%